Coxiella burnetii in slaughterhouses in Brazil: A public health concern - Ribeiro Mioni, Mateus de Souza [UNESP]; Costa, Francisco Borges; Devide Ribeiro, Bruna Leticia [UNESP]; Reis Teixeira, Wanderson Sirley [UNESP]; Pelicia, Vanessa Cristina [UNESP]; Labruna, Marcelo Bahia; Rousset, Elodie; Sidi-Boumedine, Karim; Thiery, Richard; Megid, Jane [UNESP] (Public Library Science, 2020)
Q fever is an important zoonosis, yet it is often neglected and can present large outbreaks, as observed in the Netherlands. In the past few years, cases of Q fever have been described in Brazil; however, the epidemiological situation of Q fever in ruminants, the main reservoir of the pathogen, is unknown in this country. Our study aimed to estimate the prevalence of C. burnetii in cattle sent to slaughterhouses using an immunofluorescence assay (IFA) and quantitative real-time PCR (qPCR). From 1515 cattle serum samples collected from nine slaughterhouses, 23.8% (360/1515) were serologically positive by IFA (cutoff titer>1:64), indicating past or recent exposure to C. burnetii infection. Among the 54 cities sampled during the study, 83.3% (45/54) had at least one seropositive animal. Subsequently, all seropositive samples were submitted to qPCR for C. burnetii DNA, and 12.2% (44/360) of the sera were qPCR positive, which indicates bacteremia and suggests active or recent infection. The results highlight the risk for abattoir workers that results from exposure to contaminated aerosols produced during slaughter procedures. Moreover, the heat maps that were construction from the positive samples demonstrate the widespread distribution of C. burnetii in the State of Sao Paulo, Brazil and denotes the need for surveillance and preventive measures to reduce the prevalence in cattle.